Bitumen fluxes of vegetable origin - Gawel, I.; Pilat, J.; Radziszewski, P.; Niczke, L.; Krol, J.; Sarnowski, M. (Polimery, 2021)
Methods of preparation of bitumen fluxes from rapeseed and linseed oil methyl esters were developed. The methods consist in the catalytic oxidation of vegetable oil methyl esters in the absence or presence of peroxides as the accelerators. The products obtained can be used as environmentally friendly bitumen fluxes. The rapeseed oil methyl ester has to be oxidized at elevated temperature in the presence of a catalyst. Linseed oil methyl ester does not need pre-oxidation before mixing with bitumen, but mixing with the catalyst is necessary. Contrary to conventional bitumen solvents, the fluxes are not volatile and have an ignition point of approximately 200°, so they do not raise safety problems. The hardening of the fluxed bituminous binder is going not by evaporation of the flux but by oxidative polymerization in the presence of a catalyst. The use of the fluxes let considerably reduce the mixing or spreading temperature of the binder, as well as the compacting temperature of the binder-aggregate mix.